2021
DOI: 10.1186/s12951-021-00793-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly glycosylated MUC1 mediates high affinity L-selectin binding at the human endometrial surface

Abstract: Background Sialyl-Lewis X/L-selectin high affinity binding interactions between transmembrane O-glycosylated mucins proteins and the embryo have been implicated in implantation processes within the human reproductive system. However, the adhesive properties of these mucins at the endometrial cell surface are difficult to resolve due to known discrepancies between in vivo models and the human reproductive system and a lack of sensitivity in current in vitro models. To overcome these limitations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…A widely proposed marker for endometrial receptivity is the high molecular weight transmembrane glycoprotein MUC1. MUC1 is a highly glycosylated protein whose expression in the luminal and glandular epithelium is regulated by progesterone and pro-inflammatory cytokines (i.e., TNF-α) [ 179 , 180 , 181 , 182 , 183 ]. While in other mammals MUC1 expression is down-regulated during the peri-implantation period in order to facilitate embryo attachment to the endometrium [ 184 , 185 , 186 ], in humans, its mRNA and protein levels increase during the secretory phase [ 151 , 152 ].…”
Section: Biochemical Markers and Molecular Mediators Of Endometrial R...mentioning
confidence: 99%
“…A widely proposed marker for endometrial receptivity is the high molecular weight transmembrane glycoprotein MUC1. MUC1 is a highly glycosylated protein whose expression in the luminal and glandular epithelium is regulated by progesterone and pro-inflammatory cytokines (i.e., TNF-α) [ 179 , 180 , 181 , 182 , 183 ]. While in other mammals MUC1 expression is down-regulated during the peri-implantation period in order to facilitate embryo attachment to the endometrium [ 184 , 185 , 186 ], in humans, its mRNA and protein levels increase during the secretory phase [ 151 , 152 ].…”
Section: Biochemical Markers and Molecular Mediators Of Endometrial R...mentioning
confidence: 99%
“…Given that β 1-integrin is highly expressed in the decidua [32], APN/CD13 may be involved in implantation and/or invasion of blastocysts. Some alternative mechanisms of blastocyst attachment on the endometrial cell surface were shown as follows [49]: mucin1, a highly glycosylated polymeric protein contributes to cellular adhesive properties, which may function to facilitate blastocyst binding to the endometrial cell surface, but its action is through the L-selectin/sialyl-Lewis x adhesion system, and is not directly involved in binding between blastocyst and endometrial cells [50]. Integrins are transmembrane glycoproteins, which mediate cell-to-cell and cell-toextracellular matrix (ECM) adhesion.…”
Section: Apn/cd13 In Implantationmentioning
confidence: 99%
“…Although the expression of sLe x in normal human tissues is supposed to be very low, some clues indicate its expression in oral mucosa and breast tissues [ 56 ] and in heart, kidney, and lung tissues ( , 2 August 2021). sLe x is also found in highly glycosylated mucins and sphingolipids in their non-reducing terminal structures [ 57 ]. It had initially been recognized as a tumor-associated antigen by the monoclonal antibody CSLEX1, which reacts specifically with various tumor tissues [ 58 ].…”
Section: Distribution Of Glycan Receptors For Muv In the Human Bodymentioning
confidence: 99%